Influence of Silver (Ag) Addition on the Morphological and Thermal Characteristics of NiO-SDC Carbonate Composite Anode - Kei Hoa, Ng; Abd.Rahman, Hamimah; Rao Somalu, Mahendra (International Journal of Integrated Engineering, 2018)
Addition of silver (Ag) as an electro-catalyst has been widely investigated to enhance the cathode performance for intermediate-to-low temperature SOFCs. Nevertheless, Ag is seldom incorporated into composite anode materials, especially for low temperature application. Therefore, this study aims to investigate the effects of small amount of Ag on the microstructure and thermal behaviour of NiO-SDC carbonate (NiO-SDCC) composite pellets. NiO-SDCC composite anode powder was prepared through fast milling method. Subsequently, small amount of Ag (1, 3, and 5 wt.%) was added into NiO-SDCC composite powder via ball milling. The pellets were manually pressed and sintered at 600 Â°C. Characterisation of the composite anodes include X-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), energy dispersive spectroscopy (EDS), scanning electron microscopy (SEM), dilatometry and porosity measurement. NiO-SDCC had maintained good chemical compatibility regardless of Ag loading. FTIR analysis also confirmed the existence of carbonates, suggesting Ag did not influence the carbonate bonding in all NiO-SDCC. Nonetheless, the porosity of all composite anodes was found within the acceptable range for good anodic performance (20-40%). The thermal expansion of the composite samples matched well with the SDCC electrolyte. This indicates the that addition of small Ag loading into NiO-SDCC is within the acceptable range that had demonstrated promising potential as LTSOFC composite anode.